Association of Hamstring Tightness with Lower Extremity Injuries in Athletes (Analytical Cross-Sectional Study) - Rafia Imtiaz, Asma Sattar, Anum Qaiser, Hanan Azfar, Kiran Haq, Syeda Amna Bukhari, Kanwal Fatima, Hafiza Rabia Javed, Hira Rafique, Intsam Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Flexibility if muscle is required for normal bio-mechanical functioning. Muscle tightness results from reduced capability of muscle to modify its shape during movement which results in decreased ROM. Hamstring tightness is one of the cause of hamstring injuries in athletes which leads to slowed recovery and compromises performance of athlete in the field. Objective: To find the association of hamstring tightness with lower extremity injuries in athletes. Methodology: The study was conducted on 141 athletes out of those 61 were cricketers and 80 were footballers. This study was conducted from January to May 2023. Convenient sampling was used and participants were selected from different football and cricket clubs of Lahore on the basis of inclusion and exclusion criteria. Nordic questionnaire was used to determine the lower extremity injuries and active knee extension test use to measure the hamstring tightness in athletes. Statistical data was analyzed by using SPSS version 26. Result: The results showed negative correlation between Active knee Extension test and lower extremity injuries as the value of Pearson Correlation coefficient was r = -0.204. The mean±SD for Active knee Extension test was 1.31± 0.456 while that of Lower extremity Injury level was 1.28±0.56. There was significant association between AKE test and Knee pain and LBP as P-value of 0.047 amd 0.048 was obtained respectively, while there was no significant association seen between AKE test and lower extremity Injury level as p- value of 0.34 was obtined. The p-value represented that null hypothesis is accepted. Conclusion: On the basis of results Hamstring tightness is not found to be associated with Lower Extremity Injuries. While hamstring tightness could cause knee pain and low back pain in athletes. So maintaining the flexibility of hamstring in athletes could reduce the knee pain and LBP and will enhance their participation in sports. Keywords: Hamstring tightness,Nordic questionnaire ,active knee extension test.